Escore de Apgar: história e importância na medicina veterinária - Vassalo, Flávia Gardilin [UNESP] (2014)
The Apgar score is widely used in hospitals around the world as the best method for clinical evaluation of the newborn immediately after delivery. In veterinary medicine studies have been developed to provide effective aid in the identification of risk newborns. The score is used to identify high-risk neonates requiring medical attention, especially in the first minutes of life, promoting a faster and more efficient response.